2019
DOI: 10.1177/1754337119840848
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surrogate 50th percentile human headforms to an adult male sample using three-dimensional modeling and principal component analysis

Abstract: Ice hockey helmets are required to be impact tested while mounted to a surrogate 50th percentile adult male headform. However, head shape and size can vary substantially from user to user. Furthermore, the contact area between a headform and helmet interior has been identified as an important factor affecting the protective capabilities of a helmet. The objective of this study was to compare quantitative measures of head shapes between three 50th percentile adult male headforms and a sample of adult human subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The geometry and stiffness of the Hybrid-III neck are different from a live person and unbiased neckforms [28]. Similarly, 50th percentile Hybrid-III headforms do not represent realistically the geometry and helmet fit for people [29,30]. The larger diameters and irregularities of a live person's head would be expected to increase the effective (total) drag coefficient (C T ) in unhelmeted falls and would reduce the differences between unhelmeted and helmeted tests.…”
Section: Limitationsmentioning
confidence: 99%
“…The geometry and stiffness of the Hybrid-III neck are different from a live person and unbiased neckforms [28]. Similarly, 50th percentile Hybrid-III headforms do not represent realistically the geometry and helmet fit for people [29,30]. The larger diameters and irregularities of a live person's head would be expected to increase the effective (total) drag coefficient (C T ) in unhelmeted falls and would reduce the differences between unhelmeted and helmeted tests.…”
Section: Limitationsmentioning
confidence: 99%
“…14 This fallacy is highlighted by a recent study, where differences in head shape were observed between a sample of adult males and standard HFs with the anthropometrics of a 50th percentile adult male. 15 It should be noted that the Hybrid III HF was designed using the average cranial measurements of a collection of adult Caucasian male skulls, 16 and the NOCSAE was designed based on the average anthropometrics of 13 cadaver heads within the size range of the most popular football helmet size. 17 With the growing accessibility and continued advancements in three-dimensional (3D) scanning technologies, perhaps updating the shape and dimensions of the HFs with a larger, more biofidelic data set is warranted.…”
Section: Introductionmentioning
confidence: 99%